Fulfilling the Regenerative Potential of Higher Education: A Collaborative Auto-Ethnography - Koen Rens Wessels; Lotte Grünwald (MDPI AG, 2023)
Moving towards sustainable futures in which human and natural systems increasingly flourish together asks not only for technological innovation but also for social, cultural, psychological, and spiritual transformation. Regenerative education is an upcoming strand of theory and practice seeking to understand the enabling role educational systems can fulfill in this process. This paper aims to advance the notion of regenerative education from the perspective of two regenerative principles: (1) living the question of vocation and (2) embracing emergence. To do so, we-as a teacher-researcher and a student-researcher-engage in collaborative auto-ethnography against the background of a regenerative educational experiment we participated in together, which we refer to as "Graduate with Hope". Our collaborative auto-ethnographic process was built around the practices of journaling and diffractive letter conversation. Through it, we meditate how (1) fostering a regenerative educational experience asks for the embrace of the pedagogical paradoxes of structure, shared agency, educational space, and transformation, (2) embracing these paradoxes can be confrontational and trigger inner development, and (3) sustaining commitment in this context asks for an ongoing practice of "talking the walk". These perspectives can inspire educational professionals to design for, engage in, and study regenerative forms of education.